The first step is to combine like terms on the left-hand side of the equation. Doing this gives us
![((1)/(5)+3)x=2x+42](https://img.qammunity.org/2023/formulas/mathematics/college/qfrnruhxethm0yfn0pak44mp4ujywts2pv.png)
![\Rightarrow(16)/(5)x=2x+42](https://img.qammunity.org/2023/formulas/mathematics/college/y3fa60d0jai94vj9awd3w1i0hxljl53fkj.png)
Now we subtract 2x from both sides and we get
![((16)/(5)-2)x=42](https://img.qammunity.org/2023/formulas/mathematics/college/oemdfsal1nw1vbymkuocytn581pq8ghx9l.png)
![\Rightarrow(6)/(5)x=42](https://img.qammunity.org/2023/formulas/mathematics/college/57ee39xyw2h1vr9vo5wzr7fsd4q8jxyxf5.png)
And finally, we multiply both sides of the equation by the recipricol of 6 / 5 and this gives
![(5)/(6)*(6)/(5)x=42*(5)/(6)](https://img.qammunity.org/2023/formulas/mathematics/college/yjkd334zzcg71c3etqv5noxkqy93s6o0t6.png)
which simplifies to
![\textcolor{#FF7968}{x=35}\text{\textcolor{#FF7968}{. }}](https://img.qammunity.org/2023/formulas/mathematics/college/mdw5l1e8vjp5oqzf00xnnlovvousp9djiz.png)
Hence, our answer is x = 35.